PREPARING THE FUTURE EDUCATOR TO THE CREATION OF AUGMENTED REALITY EXCURSIONS IN LOCAL EDUCATIONAL ENVIRONMENTS - Denysenko, Veronika; Borysenko, Nataliia; Sydorenko, Natalia; Hrytsenko, Iryna (Journal of Information Technologies in Education (ITE), 2021)
The article highlights the peculiarities of future teachers' preparation for the organization of augmented reality virtual excursions in educational institutions. The pedagogical conditions of preparing the future teachers in higher education institutions for virtual tours as an important form of the educational process are substantiated. The pedagogical conditions and conducting such excursions of augmented reality in local educational environments are found out on the basis of BYOD concept. The differences, advantages and disadvantages of virtual, augmented and mixed reality excursions in the educational process of pedagogical institutions are also analysed. The ways of realization of the offered approach are presented, in particular creation of the routes of excursions in education by means of QR codes, which extends the boundaries of conducting excursions in space and in time, makes this form of training more flexible and systematic. The stages and peculiarities of creation the excursion routes in local environments of educational institutions were grounded, the method of diagnostics of certain aspects of students' knowledge about the conditions of the creation of virtual excursions in local educational environments is presented. Attention is paid to the importance of future teachers' media education as they will design the educational environments including modern informative and pedagogical innovations, and the logic of the evolutionary change of computerized textbooks and online educational resources for mobile learning is proved. The concept of augmented reality opportunities opens wide prospects for the introduction of learning innovations in all forms of educational process organization.